Asbestos, leaded petrol, and other aberrations: comparing countries' regulatory responses to disapproved products and technologies. Issue 2 (7th February 2021) - Coad, Alex; Biggi, Gianluca; Giuliani, Elisa
ABSTRACT: Industrial innovation churns out increasingly unnatural products and technologies amid scientific uncertainty about their harmful effects. We argue that a quick regulatory response to the discovery that certain innovations are harmful is an important indicator for evaluating the performance of an innovation system. Using a unique hand-collected dataset, we explore the temporal geography of regulatory responses as evidenced by the years in which countries introduce bans against leaded petrol, asbestos, DDT, smoking in public places, and plastic bags, as well as introducing the driver's seatbelt obligation. We find inconsistent regulatory responses by countries across different threats, and that countries' level of economic development is often not a good predictor of early bans. Moreover, an early introduction of one ban is not strongly related to the relative performance in regard to another ban, which raises possible questions about the coherence of regulatory responses across different threats.